Cultivation of Sweet Sorghum (Sorghum bicolor (L.) Moench) and Determination of its Harvest Time to Make Use as the Raw Material for Fermentation, Practiced during Rainy Season in Dry Land of Indonesia - Naoyuki Tsuchihashi; Yusuke Goto (Plant Production Science, 2004)
We cultivated sweet sorghum cultivars – Wray, Keller and Rio – to confirm the feasibility of cultivation in dry land of Indonesia for monosodium glutamate (MSG) production. Stem yield of Wray was 4,790 ~ 6,593 g m−2. Sweet sorghum reached anthesis at 73 days after sowing (DAS) and was harvested 3.5 months after sowing. Stem length increased to 36 DAS, then rapidly to 320 cm by 80 DAS. Stem diameter reached 18 mm by 36 DAS. Stems enlarged for 1 month, then elongated. Thinning and weeding for 1 month after sowing produced heavy-stem plants with high yield because stem length and diameter determine stem volume and yield. Stem sugar weight increased after anthesis and reached a peak at 26–33 days after anthesis (DAA). Grain grew until 26 DAA and dried. It was harvestable after 30 DAA. Stem sugar content closely correlated with Brix indicating its value as an index of sugar in stem juice. Consequently, the optimum harvest time is determined by measuring Brix after 30 DAA (103 DAS). Yields were highest in cv. Wray: stems (4,790 g m−2) and sugar (286 g m−2). The juice extraction rate was ca. 50% by single-step milling without imbibition water. Using imbibition water and multiple milling steps can provide more than 400 g m−2 of sugar with a greater than 75% juice extraction ratio. Grain yield of other cultivars was similar to cv. Wray’s 238 g m−2. Sweet sorghum could be cultivated on dry land in the rainy season.